(untitled) (Research, Society and Development, 2023)
Objective: To describe the profile of patients using isotretinoin in the outpatient clinic of a private university in Teresina; patient profiles according to sex, age and acne classification; identify socioeconomic factors and psychological conditions related to adherence to treatment with isotretinoin; determine social behaviors adopted by patients using isotretinoin; verify the existence and adherence to previous treatments. Methods: This is an analysis of data contained in medical records of patients from the Dermatology outpatient clinic of a private university in Piauí who sought care from January 2021 to August 2022 and are using isotretinoin for the treatment of Acne, regardless of sex or age. Results: Thirty patients regularly monitored at the research site participated in this study, 56.6% (17) female and 43.3% (13) male. The overall mean age of the patients was 21.9 ± 4.0 years and the median was 21 years. The minimum age was 18 years and the maximum 36 years. As for the age group, the distribution shows that 47% of the patients are between 18 and 20 years old. Conclusion: It was observed in this study that the profile of patients treated with acne in this location is, therefore, female patients, aged approximately 18 to 20 years, with moderate inflammatory acne, who continued to be treated with Isotretinoin and contraceptives.